Climatic index of pasture growth in Rio Grande do Sul State, Brazil - Mota, F. S. da; Berny, Z. B.; Mota, J. F.A.S. da (Pesquisa Agropecuaria Brasileira, 2014)
The climatic index of pasture growth, of Fitzpatrick & Nix, was tested and applied with good results to Rio Grande do Sul State, Brazil. An exponential regression equation Y = 353,1 (e1.40x) where x is the climatic index of growth of tropical grasses, can be used to estimate the dry matter yield of natural grasslands, using average air temperature, rainfall and shunshine. Tables were developed for the quick determination of the thermal index for each group of forages, and the light index, both indexes being necessary for the climatic index calculation. The normal, monthly climatic index, for ten locations within the State was determined as well as the frequency of its different values for a period of 30 years, at Uruguaiana and São Luiz Gonzaga. A low climatic potential for the productivity of natural grasslands is a definitive characteristic of Rio Grande do Sul State, in winter and in dry summers. Hay can be obtained from the native grassland itself, in summer, and used in winter as feed supplement. There is a good climatic potentiality along all the year for the temperate grasses and legumes, but no adequate climate for tropical legumes during the coldest months of the winter.